Electricity and magnetism - Bleaney, B. I.; World Book, Inc.; Two-Can (Firm) (Oxford : At the clarendon, 1957)
Presents information on the nature and properties of electricity and magnetism and describes experiments to demonstrate how they work. Includes a multimedia disk containing activities, puzzles, games, and more experiments.
Includes index.
Keywords: Electricity -- Juvenile literature; Magnetism -- Juvenile literature; Electricity -- Experiments -- Data processing -- Juvenile literature; Magnetism -- Experiments -- Data processing -- Juvenile literature; Electricity; Electricity -- Experiments; Magnetism; Magnetism -- Experiments; Experiments